Nonlinear association between stress hyperglycemia ratio and severe consciousness disorder in acute ischemic stroke: A MIMIC retrospective analysis - Zhangling Long; Shuang Liao; Ying Chen (PLoS ONE, 2025)
Background The stress hyperglycemia ratio (SHR) has been extensively studied; however, its association with severe consciousness disorder (Glasgow Coma Scale [GCS] ≤ 8) in patients with acute ischemic stroke (AIS) remains unclear. This study aimed to evaluate the association between SHR and GCS ≤ 8 in AIS as well as its relationship with long-term mortality. Methods This retrospective cohort study based on the MIMIC database. The primary outcome was GCS ≤ 8, and the secondary outcome was long-term mortality. The Cox proportional risk model was used to evaluate the relationship between SHR and outcome, and the restricted cubic spline (RCS) method was used to explore the potential nonlinear relationship between SHR and outcome. In addition, Kaplan-Meier curves were used to assess the differences between SHR levels and the incidence of each outcome. Results In this study, the overall incidence of GCS ≤ 8 and long-term mortality were 8.10% and 28.75%, respectively. Multivariate Cox regression analysis showed that SHR was associated with GCS ≤ 8 (HR = 1.52, 95%CI: 1.09–2.14, P = 0.015) and long-term mortality (HR = 1.32, 95%CI: 1.07–1.61, P < 0.0001), and RCS analysis showed a significant non-linear relationship between SHR and GCS ≤ 8 (P for non-linear <0.001), and an approximately linear relationship with long-term mortality (P for non-linear = 0.149). The Kaplan-Meier curve further confirmed that the incidence of GCS ≤ 8 and long-term mortality were significantly higher in patients with high SHR than in those with medium and low SHR (log-rank P < 0.001). Conclusions Elevated SHR was associated with GCS ≤ 8 and long-term mortality in patients with AIS, with a nonlinear relationship for GCS ≤ 8. Further studies are required to confirm these results.